Criminalization of Online Gender-Based Violence (OGBV): Challenges and Solutions in Indonesian Criminal Law - Hukumu, Sahrul; Syahrir, Mukum; Lukum, Abdul Fatah (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
Online Gender-Based Violence (OGBV) is an escalating phenomenon in Indonesia, driven by the advancement of digital technology, which enables perpetrators to commit various forms of gender-based violence through online platforms. Data from the National Commission on Violence Against Women (Komnas Perempuan) indicate a sharp rise in OGBV cases, from 1,200 cases in 2018 to 8,500 cases in 2023, suggesting that existing regulations remain insufficient in providing adequate protection for victims. This study aims to analyze the challenges in the criminalization of OGBV in Indonesia and to evaluate the effectiveness of existing regulations, particularly the Electronic Information and Transactions Law (UU ITE) and the Indonesian Penal Code (KUHP). A juridical approach with qualitative analysis is employed, incorporating an examination of current regulations, case studies of court rulings, and interviews with victims and law enforcement officials. The findings reveal that sanctions imposed on perpetrators remain relatively lenient, with only 18% of reported cases being processed by law enforcement, and less than 6% resulting in convictions. Furthermore, existing regulations do not comprehensively address the various forms of OGBV, making it challenging for victims to seek justice. This study underscores the necessity for a more specific and gender-sensitive revision of criminal law to enhance victim protection. The findings are expected to serve as a foundation for policymakers in formulating more effective regulations to combat OGBV in Indonesia.